Nanomedicine Particles Associated With Chemical Exchange Saturation Transfer Contrast Agents in Biomedical Applications - Jia, Yanlong; Geng, Kuan; Cheng, Yan; Li, Yan; Chen, Yuanfeng; Wu, Renhua (Frontiers in Chemistry, 2020)
Theranostic agents are particles containing both diagnostic and medicinal agents in a single platform. Theranostic approaches often employ nanomedicine because loading both imaging probes and medicinal drugs onto nanomedicine particles is relatively straightforward, which can simultaneously provide diagnostic and medicinal capabilities within a single agent. Such systems have recently been described as nanotheranostic. Currently, nanotheranostic particles incorporating medicinal drugs are being widely explored with multiple imaging methods, including computed tomography, positron emission tomography, single-photon emission computed tomography, magnetic resonance imaging, and fluorescence imaging. However, most of these particles are metal-based multifunctional nanotheranostic agents, which pose potential toxicity or radiation risks. Hence, alternative non-metallic and biocompatible nanotheranostic agents are urgently needed. Recently, nanotheranostic agents that combine medicinal drugs and chemical exchange saturated transfer (CEST) contrast agents have shown good promise because CEST imaging technology can utilize the frequency-selective radiofrequency pulse from exchangeable protons to indirectly image without requiring metals or radioactive agents. In this review, we mainly describe the fundamental principles of CEST imaging, features of nanomedicine particles, potential applications of nanotheranostic agents, and the opportunities and challenges associated with clinical transformations.